POLITICAL INEQUITY AND THE RESURGENCE OF ETHNIC NATIONALISM IN NIGERIA: AN ANALYSIS OF THE INDIGENOUS PEOPLE OF BIAFRA (IPOB) - Akama, Harrison Eko (African Journal of Social and Behavioural Sciences, 2024)
Ethnic nationalism resurgence was manifested in the renewed demand for Biafra by the secessionist organizations especially the Indigenous People of Biafra (IPOB). The study therefore, examined political inequity and ethnic nationalism in Nigeria with particular reference to the Indigenous People of Biafra (IPOB). The theory of political instrumentalism advanced by the American philosopher John Dewey in 1949 formed the theoretical basis for this study. The study adopted survey research design. Data were derived from primary and secondary sources. The population of the study constituted the member of Indigenous People of Biafra (IPOB) in the old Eastern region comprising of the current South East and South- South geopolitical zones. Convenience sampling technique was used to select a sample of 400 respondents for the study. The data generated were analysed using descriptive statistics and Pearson Chi-square. The study found that ethnic politics has fuelled political inequity in Nigeria. Ethnic politics has resulted to dangerous forms of ethnic nationalism and increases political inequalities in Nigeria. Competition for state power and natural resources were also found to have enhanced ethnic nationalism in Nigeria. The study recommends that an all, inclusive political system is the key solution. Nigeria should create an inclusive political system where ethnic and religious affiliation will no longer be a defining factor in political participation.